Estudoda sismicidade na região de Sobral - CE em 2008 - Oliveira, Paulo Henrique Sousa de (2010)
The town of Sobral is located at the northwest part of the Ceará State, 250 km away from its capital, Fortaleza. In January 2008, an intense seismic activity began near Sobral with one event with magnitude 4,2mb on May 21. Since the start of its seismic activity, all events were recorded by the SBBR station (located on EMBRAPA Caprinos Farm), which operates in the region since August 2007. After this event, monitoring the seismic activity was carried out with the deployment of a local three component digital seismographic network, from June 5, 2008 until September 24. Initially, this network was composed of six seismographic stations. Later additional five stations were deployed until August 26 2008. This local network detected approximately 2,800 earthquakes. In this study we analyzed 581 earthquakes recorded by at least three stations for hypocentral and focal mechanism determination, and to contribute to a better explanation of the seismicity which in this region. To determine the hypocenters, we used a half-space model, with vP = 6,00 km/s and vP/vS = 1,71. From the hypocentral determination, it was revealed an active seismic zone with depth ranging between 1 and 8 km, 6 km long in E - W direction. The determination of fault planes and focal mechanism was obtained using the programs FPFIT and PLAN, which allowed comparison between their respective results in order to obtain more accurate results. A set of 24 earthquakes were selected to determine fault using PLAN planes and focal mechanisms using FPFIT. With the aid of detailed map of hypocenters this set, it was possible to identify three structures. Therefore, the set of 24 earthquakes were divided into three subsets. The type of mechanism was predominantly strike-slip with a dextral direction. Although the region has two tectonic structures near the site of the study area: the Café- Ipueiras Fault (normal fault) and the Sobral-Pedro II Lineament (dextral strike-slip fault) it was not possible to correlate the seismicity founded with those structures